METTL3 Regulates Ossification of the Posterior Longitudinal Ligament via the lncRNA XIST/miR-302a-3p/USP8 Axis - Yuan, Xiaoqiu; Shi, Lei; Guo, Yongfei; Sun, Jingchuan; Miao, Jinhao; Shi, Jiangang; Chen, Yu (Frontiers in Cell and Developmental Biology, 2021)
The prevalence of ossification of the posterior longitudinal ligament (OPLL) is increasing, and currently there is no effective medical treatment for OPLL. Methyltransferase like 3 (METTL3), one of the components of the m6A methyltransferase complex, regulates gene expression via modification of mRNA. Although METTL3 has been implicated in a variety of diseases, its role in OPLL remains to be elucidated. Primary ligament fibroblasts were used in this study. To investigate the role of METTL3 in OPLL, METTL3 was silenced or overexpressed. m6A RNA methylation was measured by commercially available kits. Luciferase reporter assay was performed to investigate the binding of miR-302a-3p and METTL3, and the binding of miR-302a-3p and USP8. Quantitative RT-PCR and western blots were used to evaluate mRNA and protein expression, respectively. OPLL increases METTL3 and its m6A modification. Overexpressing METTL3 significantly promoted osteogenic differentiation of primary ligament fibroblasts. Mechanism study showed that METTL3 increased m6A methylation of lncRNA X-inactive specific transcript (XIST). Further study showed that lncRNA XIST regulates osteogenic differentiation of primary ligament fibroblasts via miR-302a-3p, which targets ubiquitin-specific protease 8 (USP8). METTL3 enhanced osteogenic differentiation of primary ligament fibroblasts via the lncRNA XIST/miR-302a-3p/USP8 axis. The findings highlight the importance of METTL3-mediated m6A methylation of XIST in OPLL and provide new insights into therapeutic strategies for OPLL.